A new master of the cultural domain? Google's role in the transactive memory systems of advertising copywriters and art directors. (August 2019) - Barker, Richie; Atkinson, Paul
Creative practice in advertising is often lauded for its novelty, which is recognised in industry awards and other forms of peer evaluation. However, advertising is commonly required to address broad audiences, which means it needs to reflect popular and common cultural ideas. When developing ideas for a new project, advertising creatives usually undertake a research process that allows them to draw upon popular culture texts and previous advertisements. In the pre-digital era, this activity largely depended on the creative's relationship to their social milieu, but following the arrival of the Internet and the search engine, the creative research process has expanded in scope and become much faster. However, the idea that search, and we refer particularly to Google search, neutrally supports creative practice requires greater scrutiny. In this article, we explore how Google connects advertising creatives to cultural references by considering research on practitioners' everyday actions through the lens of transactive memory theory and models of creative process.